"Arquitextura dos afetos: escrileituras sobre desenhos de artistas-professores" - EIRÓ, Jorge (Universidade Federal do Pará, 2014)
This work invests in a narrative whose proposal is to weave a writing-artist on a plastic production – professor-drawings – of professor-artists of the Faculty of Architecture and Urbanism of the Federal University of Pará. Around these common vectors (art, teaching and architecture), we notice the occurrence of drain lines which emerge from the plastic productions that cross their subjective processes. Thus, how do their drawings involve the movement of creation-formation of these artists-professors? How are the lines of artistic creation and art teaching articulated? Hence, the desire of a deferred consideration of such images, understood as lifelines of these professors-artists. The study works with Deleuze and Guattari carthography in order to explore both their artist notebooks and professors’ diaries, proposing an artist writing-reading in the form of biographems based on Barthes. This theoretical and methodological junction is the origin of the cartographems, a concept used by this author in his master’s thesis, and used again in this thesis-scripture concerning his conception of his architexture of affections. A manner of writing that runs the risk of a scripture: visual narratives of a writing-drawing (graphein), not as a critical analysis, but as a confabulation that emphasizes poetic inventiveness and artistic creation in educational writing. The Education which is sparkled by the field of creation as the production of the difference: an educreation as policy plastic, for the artist writing creates lifestyles, aesthetics of existence, artistic and poetic concepts of the difference. A thesis-scripture conceived between writing lines and drawing lines, as will of power in the immanent field of creation.